The Effect of Adding a Large Red Chili Puree (Capsicum annuum L.) on the Physicochemical Characteristics of Yogurt - Titi Mutiara Kiranawati; Soenar Soekopitojo; Setiawan Jati Paksi Pambudi (Bulletin of Culinary Art and Hospitality, 2021)
Milk is a liquid obtained from milking dairy cows, one of the processing of milk that is to be yogurt, in general yogurt is consumed as a dessert and also as an additional food such as salad dressings, generally made by adding fruit or vegetables as a dye, flavoring and also to add benefits, one of which is the addition of a large red chili puree (capsicum annuum L) where the manufacture of yogurt with the addition of large red chili puree aims as a diversification of food products and the development of processed yogurt as a complement to foods such as sauces. The research used is experimental research using a Complete Randomized Design with five treatments and 2 times the study, then analyzed physical and chemical properties (color, viscosity, pH, antioxidant capacity and total Lactic Acid Bacteria) in yogurt addition of large red chili puree with the formula of adding 2, 4, 6, 8, and 10 percent, the total percentage of addition of large red chili puree obtained from the total main raw material in the form of milk. The data of the study results in statistical tests using ANOVA and Duncan's Multiple Range Test (DMRT). The results of the analysis showed that the addition of a large red chili puree had a noticeable difference to the color, viscosity, pH, antioxidant capacity, and total LAB. Yogurt with the addition of a large red chili puree can be used as a diversification of processed yogurt products in lieu of sambal, sauces and other complementary foods that have high benefits and can be used to add to the diversity of Indonesian cuisine.